Low-temperature redetermination of trans-cyclohexane-1,2-dicarboxylic acid - Rizal, Mohd. Razali (International Union of Crystallography, 2008)
The molecule of the title compound, C(8)H(12)O(4), lies on a twofold rotation axis that passes through the mid-points of two opposite C—C bonds of the ring. Carboxyl groups of adjacent molecules are linked by pairs of hydrogen bonds around a centre of inversion; this interaction gives rise to a chain that runs along [101].